(untitled) (Homoeopathy for All, 2026)
Homoeopathic case taking is the most important step in homoeopathic treatment. It is the process of understanding the patient as a whole, including mental, emotional, and physical symptoms. Case taking is based on scientific principles such as the law of similars, totality of symptoms, and individualization. At the same time, it requires the art of careful observation, patient listening, and understanding the patient’s feelings and expressions. Both science and art are needed to select the correct remedy. This article explains how homoeopathic case taking combines scientific knowledge with clinical skill to reach an accurate prescription and achieve long-lasting cure. It highlights case taking as the foundation of classical homoeopathic practice.